SINTESIS TENTANG INTERAKSI HUKUM ISLAM DAN HUKUM ADAT PADA MASA KOLONIAL BELANDA - Ichwan Ahnaz Alamudi (Fakultas Syariah (Syari'ah Faculty ), 2022)
This article is motivated by the Dutch legal political policy, which is known as the bamboo splitting policy which brings together face to face between customary law, Islamic law and Western law. The Dutch East Indies policy received a response from Muslims, because the Muslim community was actually in direct contact with practices as religious activities in the implementation of their teachings. This article uses a qualitative descriptive approach which is more specifically on historical aspects and uses bibliographic data sources and the type of data is secondary data. In this paper the author results that the interaction of Islamic law with customary law is described in a variety of forms. First, customary law can substantially be accepted by Islamic law as a whole, so that in the future it becomes Islamic law. Second, Islamic law has completely changed customary law, so that the validity of customary law does not apply to the next. Third, Islamic law allows customary law to apply without any effort to inhale it, this is sometimes found in the field of muamalah.Keywords: Dutch East Indies, Islamic Law, Customary Law.